FBP1, A Tumor Suppressor and Negative Regulator of Glycolysis, was Epigenetically Silenced in Pancreatic Cancer - Zhang, Bo; Qin, Yi; Shi, Si; Ji, Shunrong; Xu, Wenyan; Liu, Jiang; Long, Jiang; Liu, Chen; Liu, Liang; Ni, Quanxing; Xu, Jin; Yu, Xianjun (Current Signal Transduction Therapy, 2014)
Background: Pancreatic cancer is characterized by severe hypoxic regions, and in order to survive and proliferate under such adverse tumor microenvironment with limited supplies of nutrients and oxygen, pancreatic cancer cells must rely on their ability to reprogram canonical metabolic pathways. Thus, the understanding of pancreatic cellular metabolic transformation could shed light on the discovery of novel therapeutic approaches. Methods: The physiological role of FBP1 (Fructose-1,6-bisphosphatase 1) in pancreatic cancer proliferation and glycolysis was assessed by lentivirus mediated introduction of this enzyme into PANC-1 cells. Subsequently, the reasons accounted for the down-regulation of FBP1 were explored. Results: FPB1 was a negative regulator of pancreatic cancer cell proliferation and invasiveness. Moreover, it plays an adverse role in glycolysis by reduction in glucose uptake, lactate production and transcription in key glycolytic genes. In the end, our preliminary data indicates that FPB1 was epigenetically silenced in PANC-1 cells through DNA methylation and chromatin modifications. Conclusion: FBP1 is a negative regulator of pancreatic cancer cell proliferation, invasion and glycolysis. Moreover, FBP1 was epigenetically silenced through DNA methylation and chromatin modification.
Keywords: glycolysis